Hypothesis-generating analysis of the impact of non-damaging metabolic acidosis on the transcriptome of different cell types: Integrated stress response (ISR) modulation as general transcriptomic reaction to non-respiratory acidic stress? - Virginie Dubourg; Marie-Christin Schulz; Philipp Terpe; Stefanie Ruhs; Michael Kopf; Michael Gekle (PLoS ONE)
Extracellular pH is an important parameter influencing cell function and fate. Microenvironmental acidosis accompanies different pathological situations, including inflammation, hypoxia and ischemia. Research focussed mainly on acidification of the tumour micromilieu and the possible consequences on proliferation, migration and drug resistance. Much less is known regarding the impact of microenvironmental acidosis on the transcriptome of non-tumour cells, which are exposed to local acidosis during inflammation, hypoxia, ischemia or metabolic derailment. In the present hypothesis-generating study, we investigated the transcriptional impact of extracellular acidosis on five non-tumour cell types of human and rat origin, combining RNA-Sequencing and extensive bioinformatics analyses. For this purpose, cell type-dependent acidosis resiliences and acidosis-induced transcriptional changes within these resilience ranges were determined, using 56 biological samples. The RNA-Sequencing results were used for dual differential-expression analysis (DESeq and edgeR) and, after appropriate homology mapping, Gene Ontology enrichment analysis (g:Profiler), Ingenuity Pathway Analysis (IPA®), as well as functional enrichment analysis for predicted upstream regulators, were performed. Extracellular acidosis led to substantial, yet different, quantitative transcriptional alterations in all five cell types. Our results identify the regulator of the transcriptional activity NCOA5 as the only general acidosis-responsive gene. Although we observed a species- and cell type-dominated response regarding gene expression regulation, Gene Ontology enrichment analysis and upstream regulator analysis predicted a general acidosis response pattern. Indeed, they suggested the regulation of four general acidosis-responsive cellular networks, which comprised the integrated stress response (ISR), TGF-β signalling, NFE2L2 and TP53. Future studies will have to extend the results of our bioinformatics analyses to cell biological and cell physiological validation experiments, in order to test the refined working hypothesis here.